Las migraciones internacionales y sus efectos económicos en El Salvador - Rivera Funes, Oscar Francisco (Población y Salud en Mesoamérica, 2005)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none;">Since the 70s, in El Salvador the international migration phenomenon has included all socioeconomic sectors of the county in all departments (political-administrative division) both of urban and rural areas. The armed conflict that started in 1980 was the main cause for massive migration of Salvadorans who fled mainly from conflict zones during this decade. Unleashed by the outbreak of the war, this migration phenomenon was not programmed by economic situations as in the past. A remarkable characteristic of this phenomenon in El Salvador is the migration of urban population to remote countries, such as the United States, Australia, Canada and a few European countries. This almost planned migration in relative terms was compelled by the war. Rural population fled from the conflict by migrating towards Central American countries. Another important characteristic to be emphasized is that Salvadorans are deeply connected with their places of origin. This strong bond is reflected by their constant sending of family remittances, thus contributing significantly to reduce poverty in the most disadvantaged homes. With these remittances families are more able to cover their needs. 86.3% of remittances are used for consumption, 6.1% for education, 2.8% for medical expenses and the rest for housing, business, savings and others. This is confirmed by the results of the Survey of Homes of Multiple Purposes, which registered that 22.2% of homes receive remittances.